Nucleic acid amplification tests in digital microfluidics: the promise of next-generation point-of-care diagnostics - Duc Anh Thai; Yuguang Liu (Microsystems & Nanoengineering)
Abstract Nucleic acid amplification tests (NAAT) have long been used in laboratory facilities and recently revolutionized the field of molecular diagnostics in point-of-care testing. Digital microfluidics (DMF) has emerged as a promising tool to complete the entire NAAT workflow in a miniaturized format with minimum human intervention. Based on electric fields to manipulate independent reaction droplets, the compact DMF system could perform multiple processes simultaneously and automatically in a programmable fashion. This combination is beginning to establish powerful sample-to-answer platforms in remote or resource-limited settings. Herein, we provide a comprehensive overview of the state-of-the-art DMF technology for point-of-care NAAT. This review focused on key principles of DMF platforms and the latest trends in system integration for automated processes of nucleic acid extraction, amplification, and detection. Also, this article discusses current challenges, including control systems, scalability and throughput, as well as future prospects of DMF-based NAAT strategy for the next generation of point-of-care diagnostics.